Wine Tourist Engagement with the Winescape: Scale Development and Validation - Thomas, Ben; Quintal, Vanessa; Phau, Ian (2018)
Although the winescape has been frequently referred to in wine-related research, empirical studies that conceptualize, operationalize, and test the construct remain limited. This research sets out to develop a scale to measure the supply-related winescape attributes that influence the winery experience. Adopting scale development procedure by Churchill and De Vellis, five focus groups, two expert panels, and six individual studies that involved 1,537 participants were conducted at varied wineries in diverse wine regions across two different wine countries. The resultant 20-item winescape scale comprised seven attributes, namely, setting, atmospherics, wine quality, wine value, complementary product, signage, and service staff, and was reliable and valid. Theoretically and methodologically, the winescape scale addresses a critical need for an empirical measure that encapsulates the supply-related attributes of a winery. Managerially, it offers wine producers a diagnostic tool to evaluate their winescape, guiding their positioning and service operations in the marketplace.